The Impact of exchange rate on capital structure of non-financial companies listed on Damascus Stock Exchange Using Panel data models (Journal of Hama University, 2021)
This research examines the effect of the US dollar exchange rate against the Syrian pound on the capital structure of non-financial companies listed on the Damascus Stock Exchange, using the method of time-series cross-sectional data (panel data) by applying to a sample consisting of 4 companies (Al-Ahlia Oils Company, Al-Ahlia Transport Company, United Publishing and Advertising Company and the Agricultural Investment Engineering Company - Nama), and during the time period from 2009 to 2018, the research reached a set of conclusions, the most important of which is the influence of the capital structure of the companies studied by the consequences of economic conditions, which led to a decrease in the ratios of the capital structure during the studied period In addition to the presence of a negative and statistically significant effect of the exchange rate on the capital structure of the companies studied